PENGARUH PELAKSANAAN PERSONAL SELLING, KEPERCAYAAN PELANGGAN DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN ULANG PRODUK ASURANSI BERUPA PREMI ASURANSI (Studi pada PT. Asuransi Allianz Life Indonesia, Unit Genteng Biru Denpasar) - Luh Ketut Ari Anggarawati; Ni Wayan Eka Mitariani; I Gusti Ayu Imbayani (EMAS, 2022)
Insurance is a business that provides services to its customers. As with other businesses engaged in the service industry, insurance that operates on the basis of trust is also required to show better performance, reputation, and service. This study aims to determine and analyze the effect of the implementation of Personal Selling, Customer Trust and Service Quality on the Decision to Repurchase Insurance Products at PT. Allianz Life Insurance Indonesia, Denpasar Blue Tile Unit. The population in this study were all customers who had purchased insurance products. Sampling in this study using purposive sampling method, obtained 70 respondents. The analytical method used is Multiple Linear Regression Analysis. The results of the study indicate that Personal Selling, Customer Trust and Service Quality have a positive and significant effect on Repurchase Decisions. Further researchers are expected to use a wider sample at PT Asuransi Allianz Life Indonesia, Denpasar Blue Tile Unit to become PT Asuransi Allianz Life Indonesia in Bali.